JUMPA Vol.2 No.2 Juni 2015 PENGARUH KUALITAS DARI LINGKUNGAN FISIK, MAKANAN DAN PELAYANAN TERHADAP IMAGE RESTORAN: PENGARUH KUALITAS DARI LINGKUNGAN FISIK, MAKANAN DAN PELAYANAN TERHADAP IMAGE RESTORAN - Tommy Setiawan Ruslim Fakultas Ekonomi Universitas Tarumanagara; Mukti Rahardjo Fakultas Ekonomi Universitas Tarumanagara (Jurnal Manajemen dan Perbankan (JUMPA), 2015)
Food is a primary need for every living, with many processed ingredients, such as vegetables, fruits, meats, seafood, etc.. Many entrepreneurs have so many different ways to process, such as cooked western style, Japan, Indonesia, etc.. With the large variety of recipes, of course, made ​​so many restaurants are popping up, but not all restaurants can survive. The high competition, limited capital, the quality of food served, until the service provided is a key influence on the success of a restaurant. By doing similar research as practiced by Ryu, et al. (2011), the authors also take the Chinese food restaurant for examination: Restaurant Masakan Tio ciu Akai 45 branches Muara Karang is the study subjects. By spreading the questionnaire to 50 respondents and the data processed with PASW 18.00, by using multiple regression analysis, the result is known that quality of the physical environment as independent variable (X1), food (X2), and service (X3) have a significant effect on restaurant image (Y). With the linear regression equation is Y = 0.226 + 0.528 (X1) + 0.062 (X2) + 0.348 (X3).